A Cross-Sectional Survey on Occupational Blood and Body Fluid Exposure Risk in a Tertiary Hospital in East Malaysia - C W Ahmad CWI; Awang Lukman K; Raja Omar RM; Jeffree MS (Dove Medical Press, 2021)
Che Wan Ilmiyah C W Ahmad,1 Khamisah Awang Lukman,2,3 Raja Muhammad Raja Omar,1 Mohammad Saffree Jeffree3 1Hospital Queen Elizabeth, Kota Kinabalu, Sabah, Malaysia; 2Center for Occupational Safety and Health, Universiti Malaysia Sabah, Kota Kinabalu, Sabah, Malaysia; 3Community and Family Medicine Department, Faculty of Medicine and Health Sciences, Universiti Malaysia Sabah, Kota Kinabalu, Sabah, MalaysiaCorrespondence: Khamisah Awang Lukman Email khamisah@ums.edu.myBackground and Aim: Healthcare workers (HCWs) routinely experience occupational blood and body fluid exposure (OBBE), including percutaneous injury and splash exposure to non-intact skin. The objective of this study was to determine the prevalence of OBBE and identify associated risk factors.Methods: A cross-sectional study was performed on 334 HCWs at 9 workstations. Data were collected with a self-administered questionnaire that consisted of four parts: sociodemographic variables, work-related information, knowledge about needle stick and sharps injury and splash exposure, and information regarding previous OBBE incidents. The data were analyzed by SPSS version 22.0 software.Findings: The prevalence of OBBE was 25.1% (95% confidence interval: 20.6– 30.2), mostly due to percutaneous injuries, which were not reported to authorities. The highest proportions were among nurses and those working in the medical ward. Needle recapping practices were associated with almost a four-times higher risk of OBBE compared to no-recapping practices. HCWs who did not have any infection prevention training had a three-times higher risk of OBBE.Conclusion: Factors associated with OBBE are unsafe work practices, inadequate infection prevention training, and lack of knowledge regarding blood-borne infection. There is a need for more training and increased awareness about the risks of OBBE to reduce unsafe practices.Keywords: occupational blood and body fluid exposure, hospital